2021
DOI: 10.37939/jrmc.v25i3.1697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open versus Closed Reduction and Intramedullary Nailing in cases of Closed Tibial Shaft Fractures

Abstract: Objective: To compare the frequency of various post-operative complications in open versus closed reduction and intramedullary nailing in cases of closed tibial shaft fractures.Study Design: Comparative prospective study.Settings: Orthopedic Surgery Department, Khairpur Medical College, Khairpur Mirs.Study Duration: 1st February 2019 till 30 June 2020.Materials and Methods: Hundred and seventy patients selected for this study were divided into Group C (Closed percutaneous) and group O (Open). A closed percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…5 22 reported that the mean age of the patients was 31.1±7.9 years in close nailing group and 31.2±8.2 years was in open technique groups and they also found males in majority in both groups. On the other hand, Napar AR et al 23 found mean age of the patients 31.24 ± 6.58 years and 84.12% were males out of all study subjects. The distal femoral fractures mainly affect young males.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…5 22 reported that the mean age of the patients was 31.1±7.9 years in close nailing group and 31.2±8.2 years was in open technique groups and they also found males in majority in both groups. On the other hand, Napar AR et al 23 found mean age of the patients 31.24 ± 6.58 years and 84.12% were males out of all study subjects. The distal femoral fractures mainly affect young males.…”
Section: Discussionmentioning
confidence: 82%
“…A total of 66 cases with distal femur fractures were selected, their overall mean age was 36.23+6. 23…”
Section: Resultsmentioning
confidence: 99%